2005
DOI: 10.1897/04-117r.1
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate community response to pulse exposure with the insecticide lambda‐cyhalothrin using in‐stream mesocosms

Abstract: Pesticides are constantly being applied to agricultural catchments, but little is known about their impact on aquatic biota during natural exposure. In the present study, the impact of the pyrethroid lambda-cyhalothrin was studied in an in-stream mesocosm setup. Twice during the summer of 2002, the natural macroinvertebrate community was exposed in situ to a 30-min pulse of lambda-cyhalothrin. Pyrethroid doses were released through a modified drip set with nominal concentrations of 0.10, 1.00, and 10.0 microg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 26 publications
(53 reference statements)
2
26
0
Order By: Relevance
“…Previous studies have shown that the primary response of G. pulex and other macroinvertebrates is to enter catastrophic drift when exposed to pyrethroids (e.g. Muirhead-Thomsen, 1978;Davies and Cook, 1993;Heckmann and Friberg, 2004;Nørum et al, 2006). The observed decrease in post exposure drift rate in G. pulex with pesticide treatment might be ascribed to a reduction in activity level that make them less prone to enter drift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the primary response of G. pulex and other macroinvertebrates is to enter catastrophic drift when exposed to pyrethroids (e.g. Muirhead-Thomsen, 1978;Davies and Cook, 1993;Heckmann and Friberg, 2004;Nørum et al, 2006). The observed decrease in post exposure drift rate in G. pulex with pesticide treatment might be ascribed to a reduction in activity level that make them less prone to enter drift.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies of the toxicological impact of pyrethroids on stream macroinvertebrates have used mortality, immobilization and offset of catastrophic drift as endpoints (e.g. Farmer et al, 1995;Schulz and Liess, 1999b;Heckmann and Friberg, 2004). Despite the brief episodic occurrence and low actual concentrations of pyrethroids in natural streams, the highly toxic nature of pyrethroids may produce long term effects not readily observable.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity tests conducted at levels of lambda-cyhalothrin residues measured in water or sediment indicate potential for effects on aquatic organisms including fish and amphipods (Amweg et al , 2006Cavas and Ergene-Gozukara 2003;Gu et al 2007;Heckmann and Friberg 2005;Lawler et al 2007;Maund et al 1998;Van Wijngaarden et al 2005;Wang et al 2007;Weston et al 2004). Concerns have therefore been raised about the widespread use of lambda-cyhalothrin in California and its potential impact on aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Mesocosms have been used as venues to elucidate interactions between nutrients and aquatic plants (Carr & Chambers, 1998), algae and herbivores (Evans-White & Lamberti, 2005) and animal prey and their predators (Greenberg, 1994). Mesocosm experiments have also furthered understanding of the fate of chemicals released into the environment (Hench et al, 2003;Knapp et al, 2005), and have been used to test the effects of multiple stressors on pattern and process in aquatic systems (Belanger et al, 2004), including mine discharges (Hruska & Dube, 2004;Dube et al, 2005), surfactants (Wong et al, 2004a, b;Belanger et al, 2005), metals (Newman et al, 1987;Gold et al, 2003;Brooks et al, 2004), metalloids (Chaffin et al, 2005) and pesticides (Richardson & Perrin, 1994;Heckman & Friberg, 2005).…”
Section: Introductionmentioning
confidence: 99%